Strain‐induced deformation mechanisms of polylactide plasticized with acrylated poly(ethylene glycol) obtained by reactive extrusion. Issue 11 (5th May 2015) - Wang, Kui; Brüster, Berit; Addiego, Frédéric; Kfoury, Georgio; Hassouna, Fatima; Ruch, David; Raquez, Jean‐Marie; Dubois, Philippe
<x xml:space="preserve">Abstract</x> The deformation mechanisms of plasticized polylactide containing inclusions of poly(Acryl‐polyethylene glycol) involved chain orientation, crystallization and crystal destruction. The initial spherical inclusions were transformed into ellipsoids with a decreased density. <boxed-text content-type="graphic" id="pi4927-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>